Cinema de periferia : novas narrativas, representatividade e luta política - Anjos, Alinny Ayalla Cosmo dos (2021)
Cinema is a stage of dispute where identities and subjectivities are constructed, negotiated and perceived within culture. In this scenario, conflicts of representation in relation to the periphery concerning issues of social exclusion, racism, and historical processes, provoke discrimination against a broad sector of the Brazilian population. In the last 20 years, with the ease of access to the means of audiovisual production, together with public and private initiatives, such as inclusion policies and video workshops, the peripheries have obtained the opportunity to elaborate their own imagetic representations of their daily lives and experiences. This research analyzes this production, starting from the interweaving and conflicts that are established between pre-existing social representations, investigating their enunciation strategies and positions, and their struggle for visibility and recognition. It aims to contribute to a state of the art on the Brazilian academic production in reference to Cinema of Periphery, in the period from 2000 to 2020. Based on the systematization of this knowledge, an unprecedented and denser understanding of the field is made available. Furthermore, by means of bibliographic research and using qualitative methodology, we proceeded to analyze the discursive formation about the periphery in Brazil and its representation in national cinema. We also reflected on the conditions of formation of this cinema and its political panorama. Finally, we referenced films, filmmakers, and peripheral collectives, and conducted an analysis of the film Ela volta na quinta (2014), by André Novais. We conclude that peripheral cinema can be one of the tools for (re)elaboration of social representations, being fundamental to confront historical devices of inequality in cinema and society.